Insurance Coverage and Utilization Improve for Latino Youth but Disparities by Heritage Group Persist Following the ACA. Issue 11 (November 2018) - Kemmick Pintor, Jessie; Chen, Jie; Alcalá, Héctor E.; Langellier, Brent A.; McKenna, Ryan M.; Roby, Dylan H.; Ortega, Alexander N.
Abstract : Objective: Latino youth experience worse access to and utilization of health care compared with non-Latino "white" youth, with inequities persisting following the implementation of the Affordable Care Act (ACA). To better understand these disparities, we examine changes in youth's access and utilization associated with the ACA for different Latino heritage groups relative to whites. Study Design: We use 6 years (2011–2016) of National Health Interview Survey data to examine Latino youth's insurance coverage and health care utilization by heritage group, nativity, and parental language. The dependent measures of utilization included well-child, emergency department, and physician visits. We used multivariable logistic regression models to estimate the odds of each dependent measure and interacted heritage group and time period [2011–2013 (pre-ACA) versus 2014–2016 (post-ACA)] to examine how changes associated with the ACA varied by group. Results: Insurance coverage and well-child visits improved among youth overall following implementation of the ACA. Although Mexican and Central or South American youth experienced the largest absolute increase in coverage, they still had high levels of uninsurance post-ACA (9.9% and 9.1%, respectively). Disparities in coverage between Puerto Rican and white youth improved, while disparities in well-child visits between Mexican and white youth worsened. Little to no movement was observed in disparities by nativity and parental language. Conclusions: Most disparities in insurance and utilization across Latino heritage groups and white youth persisted post-ACA despite significant gains within groups. Although disparities for Puerto Rican youth have improved, Mexican and Central or South American youth continue to experience disparities.